Mixed Methods Research: Application, Advantages and Challenges - Josephine Oranga (PT. Radja Intercontinental Publishing, 2025)
The mixed methods approach is a research methodology that combines qualitative and quantitative research methods in a single study to provide a more comprehensive understanding of the phenomena under study. This systematic review, thus, explores the applications, advantages and challenges associated with the utilization of the mixed methods approach through a synthesis of studies published between 2006 and 2023. Hence, the advantages of the mixed methods approach as discussed in this analysis include: comprehensive understanding of the research problem, validation of data through triangulation, flexibility and adaptability during the research process, yields rich and contextualized data, provides both depth and breadth to the study and enhances interpretation of findings. On the other hand, some of the challenges are: the need for additional financial resources and time, the need to possess expertise in both qualitative and quantitative approaches, the challenge of integrating qualitative and quantitative data and the challenge of interpreting the findings. This review, thus, concludes that the integration of both qualitative and quantitative approaches is powerful and enables researchers to tap into the strengths of both approaches (qualitative and quantitative), thereby providing a fuller, more nuanced understanding of the phenomena under study.